2019
DOI: 10.3847/2041-8213/ab53e5
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Decay in a 20 Minute Orbital Period Detached Binary with a Hydrogen-poor Low-mass White Dwarf

Abstract: We report the discovery of a detached double white dwarf binary with an orbital period of ≈ 20.6 minutes, PTF J053332.05+020911.6. The visible object in this binary, PTF J0533+0209B, is a ≈ 0.17 M mass white dwarf with a helium-dominated atmosphere containing traces of hydrogen (DBA). This object exhibits ellipsoidal variations due to tidal deformation, and is the visible component in a single-lined spectroscopic binary with a velocity semi-amplitude of K B = 618.7 ± 6.9 km s −1 . We have detected significant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 53 publications
(56 reference statements)
0
65
0
Order By: Relevance
“…One way to prepare for LISA is by developing ground-and space-based instrumentation optimized to best characterize the optically detectable portion of its source population in an efficient manner. We hope that in this work, Burdge et al (2019aBurdge et al ( , 2019bBurdge et al ( , 2020, and Coughlin et al (2020), we have demonstrated that high-speed photometers, which can obtain densely sampled high-S/N light curves with high temporal resolution, will be one of the most powerful tools for such characterization. Such instruments on 10 and 30 m class telescopes could be used to characterize binaries like ZTF J2243+5242 and ZTF J1539+5027 to 10-30 kpc, distances well matched to LISAʼs sensitivity threshold.…”
Section: Implications For Lisa and The Vromentioning
confidence: 71%
“…One way to prepare for LISA is by developing ground-and space-based instrumentation optimized to best characterize the optically detectable portion of its source population in an efficient manner. We hope that in this work, Burdge et al (2019aBurdge et al ( , 2019bBurdge et al ( , 2020, and Coughlin et al (2020), we have demonstrated that high-speed photometers, which can obtain densely sampled high-S/N light curves with high temporal resolution, will be one of the most powerful tools for such characterization. Such instruments on 10 and 30 m class telescopes could be used to characterize binaries like ZTF J2243+5242 and ZTF J1539+5027 to 10-30 kpc, distances well matched to LISAʼs sensitivity threshold.…”
Section: Implications For Lisa and The Vromentioning
confidence: 71%
“…This is the third shortest-period detached binary after J0651+2844 (Brown et al 2011) and ZTF J1539+5027 (Burdge et al 2019a). While similar in period to J0935+4411 (Kilic et al 2014) and PTF J0533+0209 (Burdge et al 2019b), J2322+0509 has a face-on orientation i = 27 • . It has no detectable light curve or binary astrometric signal; only time-series spectroscopy is able to detect its period.…”
Section: Introductionmentioning
confidence: 78%
“…We originally discovered ZTF J2130+4420, which is the brightest object in the sample, using the analysis-of-variance (AOV) algorithm (Schwarzenberg-Czerny 1996) in a search of bright sources between the WD track and the main sequence. It was later recovered by both the conditional entropy algorithm and as part of a search of the hot subdwarf catalog (Geier et al 2017) as discussed in Kupfer et al (2020b; PTF J0533+0209 was also discovered with the AOV algorithm: see Burdge et al 2019b).…”
Section: Period Findingmentioning
confidence: 97%
“…In 2018 June, using ZTF's first internal data release, we discovered the shortest-orbital-period eclipsing binary system known, ZTF J1539+5027, with an orbital period of just 6.91 minutes (Burdge et al 2019a). We originally tested the viability of a photometric selection strategy using archival Palomar Transient Factory (PTF) data (Law et al 2009), and we discovered PTF J0533+0209, a ≈20.6 minute orbital period detached helium-rich DBA WD binary (Burdge et al 2019b). Since these two discoveries, we have confirmed 13 additional short-period binary systems either spectroscopically via radial velocity shifts or photometrically if they exhibit eclipses (an unambiguous indicator of binarity).…”
Section: Introductionmentioning
confidence: 99%